KAJIAN EFEKTIVITAS SENI KARAWITAN SEBAGAI MEDIA PEMASYARAKATAN TEKNOLOGI PENGENDALIAN HAMA TERPADU (PHT) (STUDI KASUS DI DESA MULA, KECAMATAN WONOSARI, GUNUNGKIDUL) (THE EFFECTIVE LEARNING OF KARAWITAN ART AS THE WAY FOR SPREADING THE COMPACT DISEASE CONT - Iswardayati, Nani Tri (Jurnal Ilmu-Ilmu Pertanian, 2006)
The goals of this experiment are to know the specific factors that influence the precision of Karawitan as communication technology of Compact Disease Control, and to know the precision of this way in spreading Compact Disease Control that looked from the age and farmers education. The data can be got by using experiment technique done at 30 respondents that take by disarranged concept after the show is over, by using questioner. The specific factors that hoped can be found by respondents identify, this is a special indicate in Compact Disease Control power, whereas the precision of using this way illustrated from differences of respondents expression from two categories, the age and the education. The conclusion of this experiment is not to find special respondent condition that indicate the specification in response power of Compact Disease Control matter. Karawitan art is effective to be used as spreading way for Compact Disease Control Technology because all respondents know Karawitan art culture, too love and enjoy the special art power, all respondents can understand the message sense that given, not see the age and the education.